Primary hepatic mucosa-associated lymphoid tissue lymphoma: a case report and literature review - He, Tao; Zou, Jieyu (Frontiers in Oncology, 2024)
ObjectiveTo investigate the pathogenesis, clinical manifestations, imaging and pathological features, and treatment methods of primary hepatic lymphoma (PHL).Case presentationA 61-year-old male with a history of hepatitis B virus (HBV) infection presented to the hospital complaining of abdominal pain. Preoperative abdominal computed tomography (CT) revealed a mass in the right lobe of the liver, accompanied by an elevated alpha-fetoprotein (AFP) level. Consequently, hepatocellular carcinoma (HCC) was initially suspected. Following a comprehensive multidisciplinary consultation, the patient underwent an anatomical hepatectomy. Histopathological examination post-surgery confirmed the diagnosis of primary hepatic mucosa-associated lymphoid tissue (MALT) lymphoma. The patient received chemotherapy as an adjunct to surgical treatment. During the five-year follow-up period, there was no evidence of tumor recurrence.ConclusionPrimary hepatic MALT lymphoma is infrequently encountered in clinical practice. Its clinical and radiological presentations are often nonspecific, making the pathological evaluation the definitive diagnostic tool. Surgical resection, in conjunction with chemotherapy, remains the cornerstone of management for this condition. The prognosis for most patients is favorable.